Adaptation at the edge of a species' range - Barton, Nicholas H (Integrating ecology and evolution in a spatial context)
The flow of genes from the dense and well-adapted centre of a species' distribution interferes with adaptation to marginal environments, and may sharply limit a species' range. Deterministic models of a linear habitat suggest that populations could in principle adapt to very steep environmental gradients, by increasing their genetic variability. However, random fluctuations in sparse populations reduce this variance, and may be crucial in limiting the species' range.